Optimization of Activity of Bromelain - Dubey, Ruchita; Reddy, Soumya; Murthy, N.Y.S. (Asian Journal of Chemistry, 2011)
Bromelain is a crude protein extract obtained from pineapple fruit and stem, which comprises a variety of proteolytic enzymes. It applied for reduction of muscle and tissue inflammation, alleviation of bronchitis and sinusitis, as an aid in digestion and for relieving symptoms of gout. The most important application of bromelain includes meat tenderization. Pineapple was peeled and crushed to extract the juice containing soluble bromelain enzyme. Further processing includes precipitation, dialysis and ion exchange chromatography of enzyme. Ion exchange elutes (pure enzyme) reveal the activity of bromelain by titrimetric enzyme assay method. Further, the enzyme was immobilized for commercial uses. Finally, the enzyme was applied for meat tenderization to check the effectiveness of extracted bromelain. It exhibits potential therapeutic activities and other industrial uses.